2021
DOI: 10.1177/20543581211019640
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Matrix Metalloproteinases With Acute Kidney Injury Following CPB-Supported Cardiac Surgery

Abstract: Background: Cardiac surgery–associated acute kidney injury (AKI) is an adverse outcome that increases morbidity and mortality in patients undergoing cardiac surgical procedures. To date, the use of serum creatinine levels as an early indicator of AKI has limitations because of its slow rise and poor predictive accuracy for renal injury. This delay in diagnosis may lead to prolonged initiation in treatment and increased risk for adverse outcomes. Objective: This pilot study explores serum and urine matrix metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…A total of 20 relevant publications were retrieved for further assessment. Fifteen trials that enrolled a total of 431 participants met the inclusion criteria and were included in the systematic review [6,7,[11][12][13][14][15][16][17][18][19][20][21][22][23]. Two review authors (F.J., G.F.S.)…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 20 relevant publications were retrieved for further assessment. Fifteen trials that enrolled a total of 431 participants met the inclusion criteria and were included in the systematic review [6,7,[11][12][13][14][15][16][17][18][19][20][21][22][23]. Two review authors (F.J., G.F.S.)…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a high level of MMP-9 was linked to poor postoperative outcomes and was an independent risk factor for post-operative complications in 22 patients with constrictive pericarditis who underwent pericardiectomy with CPB [23]. Additionally, MMPs were discovered to be accurate biomarkers of acute kidney injury following CPB [22]. In 2008, a prospective randomized trial showed that aprotinin treatment decreased the blood levels of MMP-8 and MMP-9 during and six hours after CPB for the first time in humans [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations